2022
DOI: 10.1097/qco.0000000000000862
|View full text |Cite
|
Sign up to set email alerts
|

Siderophores: a potential role as a diagnostic for invasive fungal disease

Abstract: Purpose of reviewInvasive fungal diseases (IFDs) such as invasive aspergillosis continue to be associated with high morbidity and mortality while presenting significant diagnostic challenges. Siderophores are high-affinity Fe 3þ chelators produced by Aspergillus spp. and other fungi capable of causing IFD. Previously evaluated as a treatment target in mucormycosis, siderophores have recently emerged as new diagnostic targets for invasive aspergillosis and scedosporiosis. Here, we review the diagnostic potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 79 publications
0
11
0
Order By: Relevance
“…Gtx is an immunosuppressive fungal toxin that is secreted to the extracellular environment in response to fungal stress [ 40 ]. Studies have shown the utility of siderophores and/or gliotoxin in human blood and urine as useful biomarkers of Aspergillus infection, and we have detailed this recently [ 36 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gtx is an immunosuppressive fungal toxin that is secreted to the extracellular environment in response to fungal stress [ 40 ]. Studies have shown the utility of siderophores and/or gliotoxin in human blood and urine as useful biomarkers of Aspergillus infection, and we have detailed this recently [ 36 , 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Expedited collection of blood cultures/tissue specimens, adoption of molecular techniques [ 13 ], and multisystem imaging are essential to timely identify disseminated infections. Siderophores may also have an emerging role as an early diagnostic biomarker in IFD [ 27 ], which merits future investigations.…”
Section: Discussionmentioning
confidence: 99%
“…The fungal growth-dependent production of siderophores that mammalian hosts do not synthesize could enable the differentiation of colonization and invasion (infection) by A. fumigatus in critically ill patients. Our central hypothesis is that the transition to A. fumigatus invasion is accompanied by the appearance of fungal siderophores, as a response to an increased need for iron, in body fluids as a result of molecular leakage ( 12 ) ( Fig. 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The distinct roles of intracellular ferricrocin (Fc), hydroxyferricrocin (Hfc), extracellular fusarinine C (FsC), and triacetylfusarinine C (TafC) siderophores during A. fumigatus infection maintain iron homeostasis, conidial and hyphal iron storage, hyphal iron trafficking, reproductive and developmental processes, and oxidative stress resistance ( 6 , 8 , 10 , 11 ). Moreover, siderophores have been shown to serve as specific biomarkers of microbial infections ( 12 ). Additionally, A. fumigatus produces mycotoxins, including (among others) immunosuppressive gliotoxin (Gtx) ( 13 ), fumagillin, and fumitremorgin A ( 14 , 15 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation